2004
DOI: 10.1111/j.1365-2885.2004.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and disposition of clenbuterol in the horse

Abstract: The pharmacokinetics of clenbuterol (CLB) following a single intravenous (i.v.) and oral (p.o.) administration twice daily for 7 days were investigated in thoroughbred horses. The plasma concentrations of CLB following i.v. administration declined mono-exponentially with a median elimination half-life (t(1/2k)) of 9.2 h, area under the time-concentration curve (AUC) of 12.4 ng.h/mL, and a zero-time concentration of 1.04 ng/mL. Volume of distribution (V(d)) was 1616.0 mL/kg and plasma clearance (Cl) was 120.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…The LOQ restricted quantification of CLB in plasma beyond 96 h, but not in urine. A mono‐exponential decline was described in plasma and bi‐exponential decay in urine (Soma et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LOQ restricted quantification of CLB in plasma beyond 96 h, but not in urine. A mono‐exponential decline was described in plasma and bi‐exponential decay in urine (Soma et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…No metabolites have been described or identified in the horse (Guan et al. , 2002; Soma et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics, tissue distribution and metabolism of clenbuterol have been studied in a number of species, including human . Residual clenbuterol in meat and muscle tissue is also a matter of concern in the food industry and in connection with drug abuse .…”
Section: Introductionmentioning
confidence: 99%
“…The LLOQ for plasma and urine was 50 and 200 pg/mL, respectively. In previous pharmacokinetic studies for β 2 ‐adrenoceptor agonists in horses, the LLOQ of clenbuterol was 130 pg/mL in plasma and 500 pg/mL in urine (Soma et al ., ), and the LLOQ of terbutaline was 150 pg/mL in plasma (Törneke et al ., ). The analytical sensitivity of PCR in this study was inferior to that found in a human study, which was 10 pg/mL for plasma (Kobayashi et al ., ), but the sensitivity in the current study was sufficient to conduct pharmacokinetic analyses of PCR in horses.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of β 2 ‐adrenoreceptor agonists in horses were studied for clenbuterol (Soma et al ., ) and terbutaline (Törneke et al ., ). The CL and t1false/2λ2of PCR in this study were four times higher (0.12 L/h/kg) and three times shorter (9.2 h) than those of clenbuterol, respectively, and four times lower (1.9 L/h/kg) and three times longer (1.2 h) than those of terbutaline, respectively.…”
Section: Discussionmentioning
confidence: 99%